Comparative Food Web Analysis of Two Peruvian Bay Systems Along a Latitudinal Gradient: Resource Use and the Environmental Envelope - Del Solar, Alonso; Romagnoni, Giovanni; Kluger, Lotta C.; Céspedes, Carlos M. Salazar; Wolff, Matthias (Frontiers in Marine Science, 2022)
The coast of Peru lies within the tropics under the influence of the cold, nutrient-rich waters of the Humboldt Current and the interannual onslaught of the El Niño phenomenon. The Peruvian upwelling system is exceptionally productive and is comprised of subsystems at different scales along the coast. We aimed to understand the differences between two shallow coastal systems along a latitudinal gradient: Sechura Bay in the north (at the convergence of Humboldt and tropical waters) and Independencia Bay in the central-south (under typical upwelling conditions). We compared their biodiversity, trophic dynamics, community energetics, resource use and underlying abiotic conditions. Our analysis revealed that over the past two decades, Sechura has shown a warming trend, while Independencia has maintained its cold water conditions. Chlorophyll concentrations have risen significantly in both systems, higher values in Sechura suggesting there is an increase in local pressures that could lead to eutrophication. Trophic models of the La Niña 07/08 period revealed that both systems are bottom-up driven with high biomass and production at the lower trophic levels, though top-down controls were also shown, particularly in Sechura. While primary productivity was similar in both systems, differences were found in the structure and size of energy flows. More cycling and higher transfer efficiency were found in Independencia, where phytoplankton-based food chains played the main role in the overall dynamic. In contrast, the detritus food chain appears to be more relevant for energy flow in Sechura. Differences in biota and flow structure relate to the systems’ environmental conditions, i.e., more diverse warm-water species in the north and mostly cold water adapted species (mainly invertebrate filter-feeders and their predators) in the central-south. Catches in both systems were dominated by the diving fisheries and comprised mostly scallops (bottom-cultured), snails and fish in Sechura, and mussels, clams, crabs and fish in Independencia. Overall, system indicators suggest that Sechura is a comparatively less developed system. Independencia shall likely maintain its general highly productive system features, whereas Sechura will continue to be more frequently disturbed by El Niño and ongoing human-driven activities, reducing its overall stability and functionality. In the context of climate change, acknowledging these differences is essential for future adaptive management regimes.